Exploring the Correlation Between the Regulation of Macrophages by Regulatory T Cells and Peripheral Neuropathic Pain - Chen, Hongyu; Jiang, Liangfu; Zhang, Dupiao; Chen, Jianpeng; Luo, Xiaobin; Xie, Yutong; Han, Tao; Wang, Liang; Zhang, Zhe; Zhou, Xijie; Yan, Hede (Frontiers in Neuroscience, 2022)
Intractable pain after peripheral nerve injury has become a major concern in the field of pain. Current evidence shows that routine medications or surgical treatment is associated with inconsistent results and different curative effects. Stable and effective treatment methods in clinical practice are also lacking. The present study investigates the potential regulatory role of regulatory T cells in the differentiation of macrophages on dorsal root ganglion (DRG) and explores the mechanism of nociceptive signals in the signal transfer station.Thirty-six male Sprague Dawley rats and 18 male Nude rats, of equal weight (250-300g), were used in this study. Furthermore, we analyzed the degree of neuroma development, histology, gene, and protein expression, and compared their correlation with the ultrastructural changes of M1/M2 type differentiation of macrophages in DRG.Sciatic nerve transection (SNT) , induced the aggregation of several types of macrophages in the lumbar DRG of ordinary SD rats, implying a higher ratio of M1/M2. Following the inhibition of the M1 type polarization of macrophages, axon outgrowth increased significantly. A significantly lower average autotomy score was reported in the SNT/NUDE group (*p<0.05) and the SNT/RAPA group (@p<0.05) as compared to that of the SNT group. The SNT/NUDE group showed no noticeable neuroma formation 30 days after the nerve resection. Immunofluorescence staining revealed a significant decrease in the proportion of M1/M2 macrophages in the spinal cord DRG of the SNT/NUDE group (**p<0.001) and the SNT/RAPA group (@p<0.05) compared to the SNT group. The expression of pain-related proteins was also obviously decreased (@p<0.05, *p<0.05，**p<0.001). Also, the expression of alpha-smooth muscle actin (α-SMA), neurofilament 200 (NF-200), and nerve growth factor low-affinity receptor p75 were significantly down-regulated in the nerve tissue (@p<0.05, @@p<0.001, **p<0.001).M1/M2 type differentiation of macrophages on DRG plays a significant role in the formation of traumatic painful neuroma after neurotomy. In combination with our previous study, the results of this study suggest that regulatory T cells reduce the ratio of M1/M2 macrophages and alleviate the pain of neuroma by regulating the polarization direction of macrophages on neuroma. These findings provide key insights into developing new strategies to manage painful neuroma.